Comparison between regenerative organic Rankine cycle (RORC) and basic organic Rankine cycle (BORC) based on thermoeconomic multi-objective optimization considering exergy efficiency and levelized energy cost (LEC). (15th May 2015) - Feng, Yongqiang; Zhang, Yaning; Li, Bingxi; Yang, Jinfu; Shi, Yang
Highlights: The thermoeconomic comparison of regenerative RORC and BORC is investigated. The Pareto frontier solution with bi-objective compares with the corresponding single-objective solutions. The three-objective optimization of the RORC and BORC is studied. The RORC owns 8.1% higher exergy efficiency and 21.1% more LEC than the BORC under the Pareto-optimal solution. Abstract: Based on the thermoeconomic multi-objective optimization by using non-dominated sorting genetic algorithm (NSGA-II), considering both thermodynamic performance and economic factors, the thermoeconomic comparison of regenerative organic Rankine cycles (RORC) and basic organic Rankine cycles (BORC) are investigated. The effects of five key parameters including evaporator outlet temperature, condenser temperature, degree of superheat, pinch point temperature difference and degree of supercooling on the exergy efficiency and levelized energy cost ( LEC ) are examined. Meanwhile, the Pareto frontier solution with bi-objective for maximizing exergy efficiency and minimizing LEC is obtained and compared with the corresponding single-objective solutions. Research demonstrates that there is a significant negative correlation between thermodynamic performance and economic factors. And the optimum exergy efficiency and LEC for the Pareto-optimal solution of the RORC are 55.97% and 0.142 $/kW h, respectively, which are 8.1% higher exergy efficiency and 21.1% more LEC than that of the BORC under considered condition. Highest exergy and thermal efficiencies are accompanied with lowest net power output and worst economic performance. Furthermore, taking the net power output into account, detailed investigation on the three-objective optimization for maximizing exergy efficiency, maximizing net power output and minimizing LEC is discussed.